Online Course Design Using Iterative Workshops on Computer-Supported Collaborative Design for Engineering Design Students - Brisco, Ross; Whitfield, Robert Ian; Grierson, Hilary (Design and Technology Education: An International Journal, 2023)
Based on observations of global design classes at different institutions, students selected technologies without justification for the suitability of the technology to support their collaborative design activities. To best support students in their collaborative endeavours, a short online course in computer-supported collaborative design was developed. The process of the creation of the short online course was unique using students’ identification of their gaps in knowledge during workshops, iteratively over three years to develop a complete educational experience. Workshops were conducted with students to identify gaps in students’ knowledge that were addressed at future workshops, by filling these gaps and conducting the same gap finding activity the researchers can identify if these gaps can be filled through an educational intervention. Surveys were used to evaluate the success of the development of an online course in Computer-Supported Collaborative Design (CSCD). The method for the development of the short online course was logical and successful based on feedback from students during surveys. The outcomes of this method can have implications for those developing novel courses in familiar teaching environments or new digital media. This research has identified the interventions required to prepare students for global design projects in a novel way. Lessons from this research will support other educators to consider their course development practice.